0132 Self-reported Sleep Disturbance By Aircraft Noise Around Atlanta Airport. (12th April 2019) - Smith, Michael; Rocha, Sarah; Witte, Maryam; Basner, Mathias
Abstract: Introduction: Aircraft noise can disrupt sleep and impair recuperation. A recruitment survey for a field study on the effects of aircraft noise on sleep was sent to residents living in the vicinity of Atlanta International airport. To examine effects of aircraft noise on sleep, the survey included items on sleep quality, sleep disturbance by noise, strategies to cope with nocturnal noise and health conditions. Methods: Questionnaires were mailed to randomly selected households around Atlanta airport. Questionnaires were completed by 290 respondents (mean age 53 years, range 21-97 years; 186 women, response rate 10.1%). Outdoor aircraft noise between 22:00-07:00 ( L Night ), calculated in decibels (dB) for the dwelling of each respondent, was the main independent variable of interest. Logistic regression was performed for each dependent questionnaire response variable, adjusted for age, BMI, sex, race, marital status, income, education and employment. Results: With increasing L Night, there was significantly worse sleep quality (OR=1.04/dB; p<0.05), increased frequency of difficulty falling asleep within 30 minutes (OR=1.06/dB; p<0.01) and greater difficulty staying awake during daytime (OR=1.06/dB; p<0.05). An increase in L Night was also associated with increased noise-induced sleep disturbance (OR=1.17/dB; p<0.0001) and annoyance (OR=1.19/dB; p<0.0001), with respondents more likely to close windows to protect their sleep (OR=1.05/dB; p<0.01) and to report difficulties concentrating (OR=0.95/dB; p<0.05). There were no statistically significant effects on diagnosed sleep disorders, hearing impairment, hypertension, arrhythmia, chronic migraine or diabetes. Conclusion: The physiologic mechanisms underlying the negative effects of aircraft noise on sleep may be of relevance for the development of disease. Future public health policy should be informed by evidence of noise-induced sleep disruption, of which the current study is but a first step. Support (If Any): This research was funded by the U.S. Federal Aviation Administration Office of Environment and Energy through ASCENT, the FAA Center of Excellence for Alternative Jet Fuels and the Environment, project 017 through FAA Award Number 13-C-AJE-UPENN-004 under the supervision of Sean Doyle. Any opinions, findings, conclusions or recommendations expressed in this material are those of the authors and do not necessarily reflect the views of the FAA.